2013
DOI: 10.4103/0253-7176.112201
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-up Study of Academic Functioning and Social Adjustment in Children with Attention Deficit Hyperactivity Disorder

Abstract: Background:Attention deficit hyperactivity disorder (ADHD) persists in a majority of adolescents. It has been reported that ADHD patients have poor social functioning and risk for developing co-morbid psychiatric illnesses.Aims:To determine the retention of diagnosis of ADHD and to assess social adjustment, academic functioning and co-morbidities at follow-up.Design:Retrospective cohort study.Materials and Methods:ADHD patients of 5-14 years of age who came to the out-patient department from 2005 to 2008 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Responder group had more significant improvement in symptom reduction on VADTRS composite scores as compared with VADPRS composite scores. In a study on drug therapy of ADHD children (Garg & Arun, 2013), it was observed that the benefit was achieved within 2 to 8 weeks of initiation of atomoxetine. The dosage was used according to the weight of the patient and the maximum dose used was up to 1.4 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Responder group had more significant improvement in symptom reduction on VADTRS composite scores as compared with VADPRS composite scores. In a study on drug therapy of ADHD children (Garg & Arun, 2013), it was observed that the benefit was achieved within 2 to 8 weeks of initiation of atomoxetine. The dosage was used according to the weight of the patient and the maximum dose used was up to 1.4 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that children who had ADHD would not be able to perform well in school, and hence, lesser numbers would be able to enter professional colleges where tough entrance exams need to be cleared. [ 22 ] However, a meta-analysis of four studies evaluating academic functioning among college students with ADHD concluded that ADHD impacts academic functioning of a relatively selective sample of college students. It was also reported that college students with ADHD may represent a distinct set of individuals who have better cognitive abilities and better compensatory adaptive skills than the general population with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…VADPRS assessed symptoms including inattentive (items 1–9), hyperactivity/impulsivity (items 10–18) symptoms, and 2 comorbidities (conduct/oppositional defiant disorders, items 19–40 and anxiety/depression, (items 41–47). The VADPRS is developed based on the DSM-V ADHD diagnostic criteria to help pediatricians identify which children are at risk or not at risk for the diagnosis of ADHD symptoms and comorbidities [ 21 , 22 ] and is widely used in school or preschool aged children [ 23 , 24 ]. All symptoms were rated on a 4-point scale that indicated how frequently each symptom occurred.…”
Section: Methodsmentioning
confidence: 99%